Energy Use of Municipal Waste by Waste-to-Energy Technologies: Case Study of Slovakia - Stašková, Slavomíra; Staško, Martin; Szabo, Stanislav (International Journal of Energy Economics and Policy, 2025)
The aim of the paper is to quantify the energy potential of municipal waste in Slovakia disposed in landfills and to evaluate possible alternative ways of its utilization using waste to energy technologies, namely incineration, anaerobic digestion (AD) and landfill gas generation (LFG). This paper also analyses the current state of waste management in Slovakia, creates scenarios for waste to energy recovery and compares them with the current waste management. The aim is also to identify and compare the current options and to propose the most acceptable way of utilising municipal waste in accordance with the principles of circular economy and the fulfilment of environmental objectives in Slovakia.